Validation of commercial antimicrobial intervention technologies to control Salmonella and Shiga toxin-producing Escherichia coli (STEC) on pre-rigor, skin-on market hog carcasses and chilled pork wholesale cuts - Pozuelo Bonilla, Katia Cecilia (Kansas State University, 2021)
Even though swine-associated foodborne disease outbreaks have been reported less frequently than in other meat products, the potential that swine represent a source of Salmonella and Shiga toxin-producing Escherichia coli (STEC) infections in human beings cannot be disregarded. The control of pathogens using antimicrobial technologies during processing is of increasing interest by pork processors. The first study compared eight carcass antimicrobial washes or sprays, and six chilled subprimal/trim sprays, applied using commercial equipment and parameters, to quantify their ability to reduce Salmonella contamination in raw pork. Hogs were harvested to provide skin-on carcasses, and eight sides (per replication) were inoculated with a Salmonella cocktail (ca. 5 log CFU/cm²). Each side was treated in a commercial Chad cabinet using a spray [low-volume: 3% lactic acid (lLA), 400 ppm peracetic acid (lPAA), or acidified 400 ppm peracetic acid (laPAA)] or wash [high volume: ambient water (hAW), 400 ppm PAA (hPAA), 400 or 600 ppm hypobromous acid (hDBDMH), or 71°C water (hHW)] treatment within a randomized complete block study design. Post-treatment Salmonella reductions were compared. Chilled subprimals and trim from each side were inoculated and treated with antimicrobial sprays [AW, 400 ppm PAA, 400 ppm aPAA, 400 and 600 ppm DBDMH, or 2% LA] in a subprimal spray cabinet or ribbon mixer (trim). Reductions were determined over 14 days of vacuum packaged subprimal storage and four days of trim storage, along with lactic acid bacterial populations, TBARS and color determinations on non-inoculated products. For the exterior skin-on carcass surface treatments, hPAA, hDBDMH600, and hHW resulted in larger (P≤0.05) Salmonella reductions (2.8 to 3.1 log CFU/cm²) compared to AW (1.5 log CFU/cm²). Salmonella was reduced by 0.4-0.6 and 0.1-0.3 logs on subprimals and trim, respectively (P>0.05). Salmonella control was less evident at the chilled subprimal and trim stages of processing. None of the treatments had a negative impact on the subprimal quality factors evaluated. The second study compared the same carcass antimicrobial intervention technologies to quantify their ability to reduce STEC contamination on market hog carcasses. Hogs were harvested to provide skin-on carcass sides, and eight sides (per three replications) were inoculated with a 7-strain STEC cocktail (ca. 5 log CFU/cm²). Each side was randomly assigned to a final pre-chill wash treatment administered in a commercial Chad carcass cabinet within a randomized complete block study design. Post-treatment and post-chilling STEC reductions were compared. Post-treatment color changes were determined on lean, adipose, and skin carcass surfaces before and after chilling. The hHW, hPAA, and hDBDMH600 deluge washes achieved the greatest external surface STEC reductions (3.8, 3.4, and 3.2 log CFU/cm², respectively), and were significantly (P<0.05) more effective than the other intervention technologies, including the 1.7-log reduction achieved by the ambient water control. The carcass washes and sprays were less effective at reducing STEC populations attached to interior body cavity smooth lean tissue. None of the treatments negatively impacted instrumental carcass color. All pre-rigor carcass interventions provided beneficial Salmonella and STEC reductions, allowing processors flexibility in their operations.
Keywords: Organic acids; Meat safety; Final carcass wash; Subprimals; Critical Control Point